2018
DOI: 10.1155/2018/3260256
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil Preconditioning Attenuates Hepatic Ischemia-Reperfusion Injury in Rats via Neuronal Activation in Dorsal Vagal Complex

Abstract: Remifentanil, an ultra-short acting opiate, has been reported to protect against hepatic ischemia-reperfusion injury, which is a major cause of postoperative liver dysfunction. The objective of this study was to determine whether a central vagal pathway is involved in this protective procedure. Rat models of hepatic ischemia-reperfusion were used in the experimental procedures. The results revealed that intravenous pretreatment with remifentanil decreased serum aminotransferases and hepatic histologic damage; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, owing to its molecular structure, remifentanil primarily circulates in nonionized areas, and its liposoluble structure helps it in penetrating the blood-brain barrier and reaching a balance in this area. 13,14 Cui Cui et al designed an animal study to determine whether remifentanil provides protection against hepatic IRI through the activation of the μ-opioid receptor, and, if so, to determine whether the vagus nerve was involved in this process. In this study, it has been shown that, with hepatic preconditioning, remifentanil provides protection against IRI by activating the central vagus nerve instead of peripheral μ-opioid receptors.…”
Section: E Osimentioning
confidence: 99%
“…Furthermore, owing to its molecular structure, remifentanil primarily circulates in nonionized areas, and its liposoluble structure helps it in penetrating the blood-brain barrier and reaching a balance in this area. 13,14 Cui Cui et al designed an animal study to determine whether remifentanil provides protection against hepatic IRI through the activation of the μ-opioid receptor, and, if so, to determine whether the vagus nerve was involved in this process. In this study, it has been shown that, with hepatic preconditioning, remifentanil provides protection against IRI by activating the central vagus nerve instead of peripheral μ-opioid receptors.…”
Section: E Osimentioning
confidence: 99%
“…Similarly, remifentanil suppresses the apoptotic pathways blocking the association of TNF-α to its receptor [113]. Opioids are also strongly related to the protection from IRI in other tissues such as the liver [114,115], endothelium [116] and skeletal muscle [117,118] and involve similar mechanisms of action.…”
Section: Extra-renal Opioid Preconditioning Mechanismsmentioning
confidence: 99%
“…RFT is an ultra-short acting opioid that is rapidly degraded in the plasma and tissue by nonspecific esterases (7), and thus, has been used as an adjuvant analgesic for general anesthesia (8). It has also been shown to have a protective effect against hepatic ischemia-reperfusion injury (9). In human keratinocytes, RFT improves hydrogen peroxideinduced oxidative injury (10).…”
Section: Introductionmentioning
confidence: 99%